Effect of Pharmacogenetics Variations on Praziquantel Plasma Concentrations and Schistosomiasis Treatment Outcomes Among Infected School-Aged Children in Tanzania - Mnkugwe, Rajabu Hussein; Minzi, Omary; Kinung’hi, Safari; Kamuhabwa, Appolinary; Aklillu, Eleni (Frontiers in Pharmacology, 2021)
Studies on pharmacogenetics of praziquantel (PZQ) and its relevance on plasma drug concentrations and schistosomiasis treatment outcomes are lacking. We investigated the effect of pharmacogenetics variations of PZQ on plasma drug levels and schistosomiasis treatment outcomes among infected Tanzanian school children. A total of 340 Schistosoma mansoni infected children were enrolled and treated with single-dose PZQ. Stool samples analysis was done by thick smear Kato-Katz technique, and treatment efficacy was assessed at 3-weeks post-treatment. Safety was assessed within four hours after PZQ intake. Plasma samples were collected at four hours post-dose, and PZQ and trans-4-OH-PZQ concentrations were quantified using UPLCMS/MS. Genotyping for CYP3A4*1B, CYP3A5 (*3, *6, *7), CYP2C19 (*2, *3, *17), and CYP2C9 (*2, *3) were done by Real-Time PCR. The median age (range) of the study participants was 12 years (7-17). There was a significant association of CYP2C19 genotypes with PZQ concentrations and its metabolic ratio (trans-4-OH-PZQ/PZQ). PZQ concentration was significantly higher among children carrying CYP2C19 (*2, *3) carriers than CYP2C19 *1/*1 and CYP2C19 *17 carriers (ultra-rapid metabolizers) (p = 0.04). The metabolic ratio was significantly higher among CYP2C19*17 carriers than CYP2C19 (*2, *3) carriers (p = 0.01). No significant effect of CYP3A4, CYP3A5, CYP2C19, and CYP2C9 genotypes on treatment efficacy or adverse events were observed. Baseline infection intensity and CYP3A5 genotype were significant predictors of treatment associated-adverse events. In conclusion, CYP2C19 genotype significantly affects plasma PZQ concentration and its metabolic ratio. For the first time, we report the importance of pharmacogenetic variation for the treatment of schistosomiasis, a neglected tropical disease.